QUALITATIVE ANALYSIS OF MERCURY AND HYDROQUINONE CONTENT IN WHITENING CREAMS CIRCULATING IN BALIKPAPAN - Nishia Waya Meray; Eka Kumala Retno; Wury Damayantie; Warrantia Citta Citti Putri; Murtiyana Sari (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2022)
Whitening cream is a preparation or mixture of ingredients used on the outside of the body to brighten or change the color of the skin, resulting in clean and white skin. Many people, particularly women, use cosmetics to improve the appearance of their skin, one of which is whitening cream. Many producers saw this opportunity and added mercury and hydroquinone to increase the number of consumers because the product will be cheaper and provide faster results to their skin with these ingredients. This study aims to conduct a qualitative analysis of whitening creams circulating in Balikpapan. To achieve this goal, four samples A, B, C, and D were analyzed using the KI color test method, the flame test, and the color reagent method to determine the presence of mercury and hydroquinone.The findings of the qualitative test of the mercury and hydroquinone content in the whitening cream circulating in the city of Balikpapan revealed that three samples, namely samples B, C, and D, were known to contain mercury and two samples (samples A and D) were known to contain hydroquinone.